Sense of Community in the context of disease prevention and health promotion: A scoping review of the literature - Nicola Spezia; Sabina De Rosis; Sabina Nuti (BMC, 2024)
Abstract Background The centrality of community engagement in disease prevention and health promotion interventions highlights the need to understand the contextual factors that shape participation. Sense of Community (SoC), characterized by feelings of belonging, connection, and interdependence among members of a community, has emerged as a key component of community capacity and is therefore expected to influence engagement outcomes. However, empirical evidence is needed to assess its actual impact on community engagement. Additionally, the literature lacks a broader synthesis of the role and implications of SoC in this context. This study aims to review the empirical literature on SoC in disease prevention and health promotion, with a special focus on its association with community engagement. Methods A scoping review was conducted following the PRISMA guidelines, searching for empirical studies published between 1974 and 2023 via Scopus, Web of Science, and PubMed. Results Nineteen studies were included in the review, revealing three key themes: (1) the community to which SoC refers - among intervention participants, within community coalitions, and defined by the place of residence; (2) the interpretation of SoC, either as a generic, intuitive concept or as a theoretically defined construct; (3) the ways in which SoC is studied - as a predictor of engagement but also as an outcome of the interventions. Generic SoC among intervention participants emerged as a positive outcome and a factor contributing to engagement. However, as the scope expanded to encompass broader communities and SoC became more theoretically grounded, these dynamics shifted. SoC related to the place of residence did not exhibit significant improvement after interventions. Broader community-level SoC showed positive associations with engagement among members of community coalitions, but evidence was less consistent among the individuals targeted by interventions. Conclusions The review highlighted a scarcity of empirical research on SoC despite its recognition as a key component of community capacity. Contextualizing SoC is crucial, as its interpretation significantly influences its role in disease prevention and health promotion interventions. Further research is needed to clarify whether SoC can foster engagement at all community levels, especially among the general population. This is particularly relevant amid the current context of escalating health needs and strained traditional resources, where community engagement is increasingly essential to ensuring the sustainable delivery of disease prevention and health promotion efforts. If SoC can drive widespread engagement, it could play a pivotal role in building more proactive and autonomous health-promoting communities.